2022
DOI: 10.3390/atmos13091370
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Multipollutant Air Quality Health Index and Susceptibility Analysis Based on Mortality Risk in Beijing, China

Abstract: Air pollution places a considerable disease burden on the public. Compared with the widely applied air quality index (AQI), the air quality health index (AQHI) provides a more comprehensive measure of multiple pollutants. In this study, AQHI was constructed using environmental data, meteorological data, and the daily mortality data of Beijing residents from 2018 to 2020. Factors increasing the susceptibility of the population to the health effects of air pollution were identified to aid the construction of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The Generalized Additive Model (GAM), a traditional mode of time series analysis, was used to estimate the exposure-response relationship between regional air pollutant concentrations and daily mortality. The basic modeling strategy of time series analysis is the same as in the previous study [76]. Based on a zero concentration of air pollutants, an exposure-response model was used to calculate the excess mortality caused by the daily PM 10 pollution level during the study period, as shown in Equation ( 10):…”
Section: Excess Mortalitymentioning
confidence: 99%
“…The Generalized Additive Model (GAM), a traditional mode of time series analysis, was used to estimate the exposure-response relationship between regional air pollutant concentrations and daily mortality. The basic modeling strategy of time series analysis is the same as in the previous study [76]. Based on a zero concentration of air pollutants, an exposure-response model was used to calculate the excess mortality caused by the daily PM 10 pollution level during the study period, as shown in Equation ( 10):…”
Section: Excess Mortalitymentioning
confidence: 99%
“…Air pollution is both an environmental and a public health issue, especially in developing countries. Short-or long-term exposure to polluted environments can have serious adverse effects on human health, and air pollution is responsible for increased mortality and hospitalization rates, reduced life expectancy, and epidemics of asthma and allergies [3]. Air pollution is also an important factor affecting climate change and ecohydrological processes.…”
Section: Introduction 1background and Motivationmentioning
confidence: 99%